How do the graphenic domains terminate in activated carbons and carbon-supported metal catalysts?. (November 2020) - Vottero, Eleonora; Carosso, Michele; Jiménez-Ruiz, Mónica; Pellegrini, Riccardo; Groppo, Elena; Piovano, Andrea
Abstract: This work is focused on the determination of the most likely border morphologies in the H-terminated graphenic domains that constitute activated carbons, focusing on four different carbons and six supported-metal catalysts. Among the available characterization techniques, Inelastic Neutron Scattering spectroscopy provides detailed vibrational spectra containing the fingerprint of the terminal C-H groups of carbon materials. From the experimental spectra, we observed clear differences among carbons having different origin, and a systematic decrease in the integrated area upon metal deposition that linearly scales with the nanoparticles dispersion. Density Functional Theory simulations are fundamental to assign the experimental bands to specific species. Thus, an extended simulation work on both regular and defective aromatic models was carried out, providing the inelastic neutron scattering fingerprint of a large number of different C-H terminations. By fitting the experimental spectra with a linear combination of the simulated spectra, it was possible to quantify the concentration of each terminal C-H geometry in the samples, and to identify the species most affected by the metal nanoparticles deposition. Specific benzene rings exposing a single C-H group appear to have a decisive role in the interaction with the metal nanoparticles and their deposition procedure. Graphical abstract: Image 1